Status, problems and future directions of research in volleyball - Stankiewicz, Błażej (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose . To analyse of publications on various aspects of volleyball and identify the most promising areas of research. Material and methods . As information sources were selected journals from different databases, full-text catalogs and libraries. Results . It is noted that the selection and training process of young volleyball players largely determines the level of club and national teams. In this case, the application of modern techniques, systems and approaches to research is a key component of the success of the team and the level of training of talented volleyball players. Found that the combination of sports orientation and quality of life of young people through passion volleyball helps educate conscious attitude towards their health and desire for high professional achievements. Conclusions . Promising areas should be recognized, such as: improving orientation sessions volleyball; biomechanical prerequisites of development and realization of motor actions, adaptation of existing technical facilities for volleyball.